Moringa Leaf Dryer Oven System Using Fuzzy Logic Method - Yusril fauzan; Kartika Kartika (International Journal of Engineering, Science and Information Technology, 2023)
Moringa trees are often planted as living fences and along rice fields or paddy fields, and they also function as green plants. In addition, Moringa leaves are also known as an efficacious medicinal plant by utilizing all parts of the Moringa plant, starting from the bark, seeds, and leaves to the roots and undergoing processing operations such as drying, wilting and enzymatic oxidation. The processing of Moringa goes is carried out with a drying process that aims to speed up the processing of Moringa leaves. Tests on drying Moringa leaves are carried out in 2 ways, namely drying without using controls and drying using fuzzy rules, then, from the two tests, a comparison will be made, and conclusions will be drawn. This drying was carried out to determine how much weight loss was in dried Moringa leaves using fuzzy control with a temperature of 60 °C. The overall test results for Moringa leaves were carried out with two tests. Namely, the same results will be obtained from 180-gram Moringa leaves at 60°C and 180-gram Moringa leaves at 50°C. Temperature and time with a decrease in the percentage of age by 50% using fuzzy control. This system is supported by a type k thermocouple temperature sensor, load cell sensor, tubular heater, fan, solid state relay, keypad, I2C LCD, and Arduino mega. Two input variables must be controlled in a fish dryer: temperature and weight. At variable temperatures, the input is a type k thermocouple sensor. The output is an SSR that controls the tube heater so that the temperature of the fish dryer matches the set-point temperature. The fuzzy logic method controls the temperature when drying fish does not exceed the set point temperature.